Mixed Ligand Complexes of Cadmium with Trimethylenediamine and β-picoline using Cyclic Voltammetry Technique. - A. AL-QURASHI, MOHAMED; M. KILLA , HAMADA (Asian Journal of Chemistry, 2010)
Linear-scan and cyclic voltammograms were used to determine the overall formation constants of simple and mixed complexes of Cd(II) with β-picoline and trimethylenediamine. DeFord-Hume's treatment suggests that both the ligands form 1 : 3 high complexes separately in aqueous medium and Schaap-McMasters treatment reveals the presence of three mixed complexes with stoichiometry 1: 1 : 1; 1 : 1 : 2 and 1 : 2 : 1 in the same medium as for the simple complexes. The formation constants of mixed complexes were calculated statistically and compared with the observed values. The equilibria between the mixed ligand species in solution and their equilibrium are also given.